2020
DOI: 10.24075/brsmu.2020.059
|View full text |Cite
|
Sign up to set email alerts
|

Prospective pharmacological effects of psoralen photoxidation products and their cycloadducts with aminothiols: chemoinformatic analysis

Abstract: Psoralens are medicinal photosensitizing furocoumarins which are used in photochemotherapy and photoimmunotherapy of dermatoses. Psoralen photooxidation products may be involved in therapeutic effects, but the possible mechanisms of their action remain unclear. The study was aimed to assess the prospective pharmacological effects and mechanisms of activity for six previously identified ortho–hydroxyformyl-containing psoralen photooxidation products and their cycloadducts with aminothiols, as well as for struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the prospective neuroprotective activity of the 6-FUmb cycloadducts with biologically abundant aminothiols (cysteine and homocysteine) was predicted using chemoinformatic analysis [24]. It is known that an elevated level and/or accumulation of homocysteine may result in a large number of neurological conditions (e.g., Alzheimer's disease, senile dementia, vascular disorders, nephropathy, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the prospective neuroprotective activity of the 6-FUmb cycloadducts with biologically abundant aminothiols (cysteine and homocysteine) was predicted using chemoinformatic analysis [24]. It is known that an elevated level and/or accumulation of homocysteine may result in a large number of neurological conditions (e.g., Alzheimer's disease, senile dementia, vascular disorders, nephropathy, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Considering the rising trend in the studies of 6-formylumbelliferone (6-FUmb) biological activities [21][22][23][24], its prospective beneficial spectral properties based on the relevance of 6-formyl vs. 8-formyl positioning [4,25], and the routine usage of 8-formylumbelliferone (8-FUmb) as a reference compound for the above-mentioned studies, we found it important to revise the Duff ortho-formylation of unsubstituted umbelliferone (Umb) and re-evaluate the 8-FUmb and 6-FUmb yields in this convenient and cost-effective reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The Z → E photoisomerization process was monitored by HPLC and spectrophotometry, and E -FCA was obtained in preparatively useful yield. Assuming a wide range of pharmacological effects previously predicted for E -FCA by means of chemoinformatic analysis [ 23 ], the preparative synthesis of E -FCA outlined in this work is particularly valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Furocoumaric acid [( Z )-3-(6-hydroxybenzofuran-5-yl)acrylic acid; Z -FCA] is an α-pyrone ring-opening (photo)product of psoralen, while furocoumarinic acid [( E )-3-(6-hydroxybenzofuran-5-yl)acrylic acid; E -FCA] is E -isomer of Z -FCA ( Scheme 1 ). Recently, a wide range of pharmacological effects was predicted for E -FCA by means of chemoinformatic analysis [ 23 ]. These effects include a number of protective (i.e., neuro-, vaso-, and radioprotective) effects, antimutagenic, anticarcinogenic, antioxidant, and anti-inflammatory activities, and even a prospective dermatologic (in particular, antipsoriatic) therapeutic activity.…”
Section: Introductionmentioning
confidence: 99%